Associations of Occupational Styrene Exposure With Risk of Encephalopathy and Unspecified Dementia: A Long-Term Follow-up Study of Workers in the Reinforced Plastics Industry. Issue 2 (17th August 2020) - Iversen, Inge Brosbøl; Mohr, Mette Skovgaard; Vestergaard, Jesper Medom; Stokholm, Zara Ann; Kolstad, Henrik Albert
Abstract: Exposure to industrial solvents has been associated with encephalopathy. Styrene is a neurotoxic industrial solvent, and we investigated the long-term risk of encephalopathy and unspecified dementia following styrene exposure. We followed 72, 465 workers in the reinforced plastics industry in Denmark (1977–2011) and identified incident cases of encephalopathy ( n = 228) and unspecified dementia ( n = 565) in national registers. Individual styrene exposure levels were modeled from information on occupation, measurements of work place styrene levels, product, process, and years of employment. Adjusted analyses were performed using a discrete survival function. A positive trend for encephalopathy ( P < 0.01) and a negative trend for unspecified dementia ( P = 0.03) were seen with cumulative styrene exposure accrued during the recent period of up to 15 years. For unspecified dementia and the combination of unspecified dementia and encephalopathy, a positive trend was indicated when applying a 30-year exposure lag ( P = 0.13 and P = 0.07). The risk patterns seen following recent exposure probably reflect diagnostic criteria for encephalopathy requiring recent industrial solvent exposure and referral bias rather than association with styrene exposure, while the increasing risk observed for unspecified dementia and the combination of encephalopathy and unspecified dementia following distant exposure indicates an increased risk of dementia following styrene exposure with a long latency period.